Pengolahan Biji Durian Menjadi Penganan yang Kaya Nutrisi untuk Mendongkrak Perekonomian Masyarakat Akibat Pandemi Covid-19 di Desa Suka Ramai Kecamatan Baiturrahman Kota Banda Aceh - Nurmasyitah Nurmasyitah; Zuraini Mahyiddin; Monawati Monawati; Indani Indani (Universitas Syiah Kuala, 2021)
Durian is one type of fruit with a pungent aroma but delicious taste. Unfortunately, the high consumption of durian is in line with the increase in durian seed waste that is just wasted. Though durian seeds contain high nutrients. This article reports on durian seed processing activities in Suka Ramai Village, Baiturrahman District, Banda Aceh City. Suka Ramai Village with the previous number of poor people was 143 residents, then due to the Covid-19 pandemic it increased to 327 residents. Therefore, this activity is aimed at boosting the community's economy. The activity is carried out in 3 days. The training provided was about processing durian seeds into delicious, nutritious, and rich food for 3 days with a different menu every day. This PKM is carried out in 2 stages, namely, the first stage is processing durian seeds into flour and useful products. The second stage is packaging and marketing of Durian Seed products that have been processed into useful food. The conclusion of this product-based community service activity has succeeded in transferring knowledge and skills to women in Sukaramai Village, Baiturrahman District, Banda Aceh City.